Evaluation of a polyethylene-candelilla coating for tangerine fruit cv. Sai Num Pung - Worawaran Roongruangsri (2018)
Tangerine fruit cv. Sai Num Pung were coated with four microemulsion wax formulations. The main ingredients were polyethylene and candelilla in ratios : 100:0, 75:25, 60:40 and 0:100 (100% PE, 75% PE, 60% PE and 0% PE). Coated and washed non-coated fruit (control) were stored in plastic baskets at 25±2°C and 87±4% RH. The accumulation of ethanol content increased with storage time. Fruit coated with 0% PE had ethanol content over 1,500 ppm after 16 days which imparted off-flavor but in other coatings, after 21 days storage while non-coated fruit never reached this value. Non-coated fruit and fruit coated with 100% PE had the highest percentage of weight loss and internal O2 but the lowest ethanol content and internal CO2. Addition of candelilla wax to polyethylene decreased the percentage of weight loss and internal O2 but increased internal CO2 and ethanol content. Coating treatments did not influence total soluble solids, titratable acidity, pH values or vitamin C content of tangerine juice. However, there were significant changes during storage. Titratable acidity and vitamin C content of all coated fruit decreased and total soluble solids and pH values increased during storage.